Zeit für das Leben - Notwendigkeit und Probleme einer zeitsensiblen Ethik - Meyer zu Hörste-Bührer, Raphaela (Ethik der Zeit - Zeiten der Ethik)

Ethik der Zeit - Zeiten der Ethik

Herausforderungen in der inklusiven Mädchenarbeit: Begleitforschung der „Inklusiven anonymen Zuflucht“ des Mädchenhaus Bielefeld e.V. - Richter, Susanne (Inklusiver Kinderschutz – Anforderungen, Herausforderungen, Perspektiven)

Distributed Control of Partial Differential Equations Using Convolutional Reinforcement Learning - Peitz, Sebastian; Stenner, Jan; Chidananda, Vikas; Wallscheid, Oliver; Brunton, Steven L.; Taira, Kunihiko (Physica D: Nonlinear Phenomena)
We present a convolutional framework which significantly reduces the complexity and thus, the computational effort for distributed reinforcement learning control of dynamical systems governed by partial differential equations (PDEs). Exploiting translational equivariances, the high-dimensional distributed control problem can be transformed into a multi-agent control problem with many identical, uncoupled agents. Furthermore, using the fact that information is transported with finite velocity in many cases, the dimension of the agents’ environment can be drastically reduced using a convolution operation over the state space of the PDE, by which we effectively tackle the curse of dimensionality otherwise present in deep reinforcement learning. In this setting, the complexity can be flexibly adjusted via the kernel width or by using a stride greater than one (meaning that we do not place an actuator at each sensor location). Moreover, scaling from smaller to larger domains – or the transfer between different domains – becomes a straightforward task requiring little effort. We demonstrate the performance of the proposed framework using several PDE examples with increasing complexity, where stabilization is achieved by training a low-dimensional deep deterministic policy gradient agent using minimal computing resources.

Kinderschutz im Wandel – methodologische Herausforderungen einer Ethnographie zur Institutionalisierung Früher Hilfen - Kelle, Helga; Edler, Amanda; Dahmen, Stephan (Zwischen Transformation und Tradierung – Qualitative Forschung zum Wandel pädagogischer Institutionen)

Der Imperativ der Biographisierung und die Ambivalenzen individueller Verantwortungszuschreibung - Dahmen, Stephan (Responsibilisierung)

Sinnvolle Ergänzung oder bewusster Bruch? - Tätigkeitsfelder im Berufsfeldpraktikum innerhalb des Lehramtsstudiums - Vogelsang, Christoph; Meier, Jana (Das Berufsfeldpraktikum als Professionalisierungselement - Grundlagen, Konzepte, Beispiele für das Lehramtsstudium)

Mediennutzung von Jugendlichen zu sozialen und politischen Fragen, schulische Aktivitäten und Lehrkräftefortbildungen - Welsandt, N.J.; Huschle, L.; Drossel, Kerstin; Deimel, D.; Abs, H.J. (ICCS 2022. Schulische Sozialisation und politische Bildung von 14-Jährigen im internationalen Vergleich)

A new mathematical formulation for the simultaneous optimization of charging infrastructure and vehicle schedules for electric bus systems - Stumpe, Miriam (Transportation Research Procedia)

Synergieeffekte zwischen Henze-Digital und der Carl Maria von Weber-Gesamtausgabe durch die bilaterale Weiterentwicklung der WeGA-WebApp - Ried, Dennis

Die Werkdatensätze von Henze-Digital als Ansätze für ein digitales Werkverzeichnis - Ried, Dennis (Die Tonkunst)

HenDi-ODD v3.0.0 - Ried, Dennis; Capelle, Irmlind; Minetti, Elena

HenDi-WebApp v3.0.0 - Ried, Dennis

‚Epitexte‘ in der Reger-Werkausgabe - Ried, Dennis (Werk und Beiwerk)

Single-step self-punching lockbolt process for aluminum sheets without pre-hole - Han, Daxin; Kappe, Fabian; Vorderbrüggen, Julian; Jendrny, Jörg; Gorr, Eugen; Meschut, Gerson (Journal of Manufacturing Processes)
Keywords: Industrial and Manufacturing Engineering; Management Science and Operations Research; Strategy and Management

Vorstellungen von Grundschulkindern zu Sterben und Tod – eine qualitative Untersuchung - Magdeburg, Lena Maria (In Alternativen denken – Kritik, Reflexion und Transformation im Sachunterricht)

Humans in XAI: Increased Reliance in Decision-Making Under Uncertainty by Using Explanation Strategies - Lammert, Olesja; Richter, Birte; Schütze, Christian; Thommes, Kirsten; Wrede, Britta (Frontiers in Behavioral Economics)

Editorial: ENT | GRENZ | UNGEN (in) der Medienpädagogik - Ade, Larissa; Breiwe, René; Dehmel, Lukas; Wolf, Karsten D.; Rummler, Klaus; Dander, Valentin; Grünberger, Nina; Schiefner-Rohs, Mandy (Zeitschrift MedienPädagogik)

Experimental investigations of uniaxial and biaxial cold stretching within PC‐films and bars using optical measurements - Hamdoun, Ayoub; Mahnken, Rolf (PAMM)
Abstract Polycarbonate (PC) is an amorphous polymer that is an extremely robust material with a high tenacity, and thus suitable for a lightweight construction with glass‐like transparency. Due to these advantageous properties, PC is often used in industry for example in medical devices, automotive headlamps, sporting equipment, electronics, and a variety of other products. PC is often subjected to uniaxial and biaxial loading conditions. Therefore, reliable material models have to take into account the various resulting experimental effects. For those reasons, we investigate PC specimens under uniaxial and biaxial loading by using different stretch rates and loading scenarios. In addition to that, we propose methods for optical measurement of local stretches to obtain the approximated local true stress. In future work, the displacement fields and the resulting reaction forces will be used for parameter identification of constitutive equations.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Multiscale simulation of polymer curing of composites combined mean-field homogenisation methods at large strains - Lenz, Peter; Mahnken, Rolf (International Journal of Solids and Structures)
Keywords: Applied Mathematics; Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science; Modeling and Simulation